Therapeutic action of streptomycin and isoniazid in experimental tuberculosis of the guinea pig - Vargas Machuca, Ramón (1956)
We have studied the therapeutic action of streptomycin and isoniazid in experimental guinea pig tuberculosis. One group was treated from the day of being inoculated with isoniazid, and sacrificed at 30 days. Two other groups were treated 30 days after being infected with streptomycin or isoniazid. and slaughtered at 60 days of infection. Inoculated guinea pigs served as controls for these experiments. The most significant events are: absence of nodule at the site of inoculation, and no injuries generalization in receptive treaty bodies the day after being inoculated group. In animals treated late, cheesy lesions in the satellite nodule inoculation and lymph, experienced no changes to account, but injuries generalization in receptive organs were discrete, and to a lesser extent than observed in controls. In all treated animals. tuberculin sensitivity significantly decreased, disappearing in some, the most in those treated with isoniazid. The tuberculin sensitivity was not present in the treated animals the day after being inoculated. Animal inoculation tests, conducted with apparently normal spleens of treated guinea pigs showed the presence of virulent organisms in a high percentage. Was observed in treated animals, local or systemic toxic reactions attributable to these chemotherapeutic agents.